The Classical Moment: Views from Seven Literatures - Holst-Warhaft, Gail; McCann, David R. (Rowman & Littlefield Publishers, 1999)
The Classical Moment is a reexamination of the concept of a supreme moment in the literatures of Greece, Mesopotamia, India, China, Japan, Korea, and Vietnam. Taking the case of Greece as its starting point, it examines what such 'moments' have in common, how they are created, and what effect they have on subsequent literary creation.